PENGEMBANGAN PEMBELAJARAN IPA (SAINS) DAN IPS DI MI - Muhammad Ngali Zainal Makmun (Jurusan PGMI FTIK IAIN Metro Lampung, 2015)
The partiality of educative orientation will make the students get harms, because they only have more knowledge in many things but have less of value systems, interests and attitudes in a positive appreciation toward what they have been known. This study is based on two cases; first how is the learning process of science and social knowledge based on integrated interconnection in Islamic elementary school?, second, What is the problem in learning process of science and social knowledge based on integrated interconnection in Islamic elementary school? The result of this study shows that learning process in the subject of science and social knowledge based on interconnected integration used three systems; justification, spirituality and learning approach based on “type integrated”. The problems of this study are there has not been standard book yet for the teachers that contains Islamic values, time management in the classroom that needs to be done strictly and well, and there are no standard provisions and regulations for certain binding policy about integrative learning with Islamic values.